2015
DOI: 10.1007/978-3-662-47672-7_80
|View full text |Cite
|
Sign up to set email alerts
|

Shortest Reconfiguration Paths in the Solution Space of Boolean Formulas

Abstract: Abstract. Given a Boolean formula and a satisfying assignment, a flip is an operation that changes the value of a variable in the assignment so that the resulting assignment remains satisfying. We study the problem of computing the shortest sequence of flips (if one exists) that transforms a given satisfying assignment s to another satisfying assignment t of a Boolean formula. Earlier work characterized the complexity of finding any (not necessarily the shortest) sequence of flips from one satisfying assignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Mouawad, Nishimura, Pathak, and Raman [133] considered shortest transformation, and obtained a trichotomy, based on both tight relations and navigable relations, a subset of tight relations. They showed that the problem is in P for formulas built from navigable relations, NP-complete for formulas built from relations that are tight but not navigable, and PSPACE-complete otherwise.…”
Section: Shortest Transformationmentioning
confidence: 99%
“…Mouawad, Nishimura, Pathak, and Raman [133] considered shortest transformation, and obtained a trichotomy, based on both tight relations and navigable relations, a subset of tight relations. They showed that the problem is in P for formulas built from navigable relations, NP-complete for formulas built from relations that are tight but not navigable, and PSPACE-complete otherwise.…”
Section: Shortest Transformationmentioning
confidence: 99%
“…Generally speaking, finding shortest transformations is much more difficult if we need a detour, which touches an element that is not in the symmetric difference of the source and target configurations. For such a detour-required case, only a few polynomial-time algorithms are known for shortest variants, e.g., satisfying assignments of a certain Boolean formulas by Mouawad et al [18], and independent sets under the TS operation for caterpillars by Yamada and Uehara [24]. Note that Matching Reconfiguration belongs to the detourrequired case; recall the example in Figure 1, where we need to use the edge in…”
Section: Exact Matching Diametermentioning
confidence: 99%
“…Recently, there has been considerable interest in the complexity of finding shortest transformations between configurations. Examples include finding a shortest transformation between triangulations of planar point sets [21] and simple polygons [1], configurations of the Rubik's cube [6], and satisfying assignments of Boolean formulas [17]. For all of these problems, except the last one, we can decide efficiently if a transformation between two given configurations exists.…”
Section: Introductionmentioning
confidence: 99%
“…Such problems (also referred to as the s − t-connectivity problems for Boolean satisfiability) have been considered extensively before [9,22,23,29,26,28]. Here we investigate the complexity of the reconfiguration versions of Boolean satisfiability problems in which the variable-clause incidence graph is planar.…”
Section: Planar Nae 3-sat Reconfigurationmentioning
confidence: 99%